Optimising the REE-Zr-Nb potential of eudialyte and its alteration products in the Ilímaussaq complex, South Greenland - Borst, Anouk Margaretha; Mortensen, Henrik Friis; Finch, Adrian Anthony (2016)
Eudialyte-group minerals are complex alkali-zirconosilicates that crystallise in peralkaline igneous rocks known as agpaitic nepheline syenites 1 . They provide important unexploited resources for rare earth elements (REE) and other critical metals such as Zr, Nb and Ta 1, 2,3,4 . Europe hosts significant eudialyte deposits in rift-related alkaline intrusions, e.g. Ilímaussaq (Greenland), Lovozero and Khibiny (Russia) and Norra Kärr (Sweden) 5 . With relatively high contents of the more critical heavy REE, and low U and Th contents compared to conventionally exploited REE phases, eudialyte is particularly attractive as a more sustainable source of REE.